2018
DOI: 10.5194/tc-12-685-2018
|View full text |Cite
|
Sign up to set email alerts
|

Floe-size distributions in laboratory ice broken by waves

Abstract: Abstract. This paper presents the analysis of floe-size distribution (FSD) data obtained in laboratory experiments of ice breaking by waves. The experiments, performed at the Large Ice Model Basin (LIMB) of the Hamburg Ship Model Basin (Hamburgische Schiffbau-Versuchsanstalt, HSVA), consisted of a number of tests in which an initially continuous, uniform ice sheet was broken by regular waves with prescribed characteristics. The floes' characteristics (surface area; minor and major axis, and orientation of equi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(88 citation statements)
references
References 38 publications
8
78
2
Order By: Relevance
“…In Bennetts et al (), floes fracture according to a strain criterion similar to ours, but the change in the FSD is calculated assuming a “split power law” distribution of floes sizes based on observations from Toyota et al (). Zhang et al () and Bennetts et al () impose behavior on fractured floe sizes that is inconsistent with results from a small‐scale model (Montiel & Squire, ) and laboratory observations (Herman et al, ), which indicate preferred sizes in the FSD resulting from wave fracture. Developing or tuning models to explicitly match “split power law” shapes may be misleading, as many observations do not show this distribution (e.g., Inoue et al, ; Paget et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In Bennetts et al (), floes fracture according to a strain criterion similar to ours, but the change in the FSD is calculated assuming a “split power law” distribution of floes sizes based on observations from Toyota et al (). Zhang et al () and Bennetts et al () impose behavior on fractured floe sizes that is inconsistent with results from a small‐scale model (Montiel & Squire, ) and laboratory observations (Herman et al, ), which indicate preferred sizes in the FSD resulting from wave fracture. Developing or tuning models to explicitly match “split power law” shapes may be misleading, as many observations do not show this distribution (e.g., Inoue et al, ; Paget et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…Recently, pan‐Arctic (Zhang et al, ) and stand‐alone (Bennetts et al, ) models which include floe size information have been demonstrated, but these impose the FSD shape or behavior rather than allowing it to emerge from physical processes acting on individual floes. Further, the power law FSD profiles used to develop these empirical parametrizations may be inconsistent with observations (Herman, ) and the physics of sea ice floes (Herman et al, ; Horvat & Tziperman, ).…”
Section: Introductionmentioning
confidence: 99%
“…The model includes a standard elasto-visco-plastic rheology (Hunke and Dukowicz, 1997), using the stress tensor formulation of Bouillon et al (2013) adapted for the C-grid used in the model. The ice strength is determined following Hibler III (1979), with the ice strength P following P = P * h e C(1−c) , where P * = 20 000 N m −2 and C = 20 are empirical positive parameters, and h is the cell-average sea ice thickness. The plastic failure threshold lies on an elliptical yield curve, with the eccentricity set to 2.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Cheng et al (2018) used the same data in an analysis of the influence of floe size on wave dispersion. Other LS-WICE results were used to study floe-size distributions in sea ice broken by waves (Herman et al, 2017(Herman et al, , 2018 as well as wave-induced collisions and floe kinematics (Li and Lubbad, 2018). A sketch of the experiment set-up is shown in Fig.…”
Section: Experiments Set-upmentioning
confidence: 99%